Raptors : the curious nature of diurnal birds of prey - Bildstein, Keith L. (Comstock Publishing Associates, a division of Cornell University Press, 2017)
Raptors are formally classified into five families and include birds--such as eagles, ospreys, kites, true hawks, buzzards, harriers, vultures, and falcons--that are familiar and recognized by many observers. These diurnal birds of prey are found on every continent except Antarctica and can thrive in seemingly inhospitable spots such as deserts and the tundra. They have powerful talons and hooked beaks for cutting and tearing meat, and keen binocular vision to aid in their hunting prowess. Because of their large size, distinctive feeding habits, and long-distance flight patterns, raptors intrigue humans and have been the subject of much general interest as well as extensive scientific research. Keith L. Bildstein has watched and studied raptors on five continents and is well prepared to explain their critical importance, not only as ecological entities but also as inspirational tokens across natural and human-dominated landscapes. His book offers a comprehensive and accessible account of raptors, including their evolutionary history, their relationships to other groups of birds, their sensory abilities, their general natural history, their breeding ecology and feeding behavior, and threats to their survival in a human-dominated world. Biologically sound but readable, Raptors is a nontechnical overview of this captivating group. It will allow naturalists, birders, hawk-watchers, science educators, schoolchildren, and the general public, along with new students in the field of raptor biology, to understand and appreciate these birds, and in so doing better protect them.